2018
DOI: 10.3390/ma11101886
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Biodegradable Plastics in the Polypropylene Recycling Process

Abstract: Recycling polymers is common due to the need to reduce the environmental impact of these materials. Polypropylene (PP) is one of the polymers called ‘commodities polymers’ and it is commonly used in a wide variety of short-term applications such as food packaging and agricultural products. That is why a large amount of PP residues that can be recycled are generated every year. However, the current increasing introduction of biodegradable polymers in the food packaging industry can negatively affect the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 49 publications
1
44
0
3
Order By: Relevance
“…The test specimens were standard rectangular specimens (80 × 10 × 4 mm 3 ) and standard tensile specimens “1BA” (length ≥ 75 mm, width of 10 mm, and thickness ≥ 2 mm) according to UNE‐EN ISO 527 . Starchy materials are water sensitive and it has been observed that TPS‐based materials performances are influenced by the humidity (i.e., mechanical and thermal properties). Therefore, all samples were conditioned 24 h at 25 ± 1 °C and 50 ± 5% HR previous to be characterized.…”
Section: Methodsmentioning
confidence: 99%
“…The test specimens were standard rectangular specimens (80 × 10 × 4 mm 3 ) and standard tensile specimens “1BA” (length ≥ 75 mm, width of 10 mm, and thickness ≥ 2 mm) according to UNE‐EN ISO 527 . Starchy materials are water sensitive and it has been observed that TPS‐based materials performances are influenced by the humidity (i.e., mechanical and thermal properties). Therefore, all samples were conditioned 24 h at 25 ± 1 °C and 50 ± 5% HR previous to be characterized.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, PP is widely used for the production of short‐term applications, which generate a huge amount of plastic waste over years which can be recovered in the form of energy or material. Fortunately, more than 70% of plastic wastes are recovered in the form of materials using industrial recycling (31% of plastic waste) and in the form of energy (41.6% of plastic waste), closing the loop of the circular economy . That means that around 8.5 million tonnes of plastics are recycled every year .…”
Section: Introductionmentioning
confidence: 99%
“…Scientists prefer polymer thermoplastics more than thermosets because of their low production cycle, lower processing costs, and high thermoplastic reparability [1,2]. Global polymer production has increased enormously to more than 330 million tons over the last five decades because polymers are widely used in industry [3][4][5][6]. In 2015, there were around 322 million tons produced worldwide, which was about 90 times higher than polymers produced in 1960.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, there were around 322 million tons produced worldwide, which was about 90 times higher than polymers produced in 1960. It was also reported that in the European Union, 58 million tons of polymers were produced and utilized, and only around 30% were recycled [3,4]. As a result of the growth in polymer production and utilization, large quantities of polymer waste are generated [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation